Sonata for the piano forte : op. 2, no. [1] composed and dedicated to Haydn by Louis van Beethoven ; edited by W. Sterndale Bennett. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Bennett, William Sterndale, 1816-1875 (editor):::Contributor:::::::::::: (United Kingdom; Leader & Cock; London, 2022)
Edition of the Piano Sonata no. 1 in F minor, op. 2, no. 1, published in the series of "Beethoven's Works" edited by William Sterndale Bennett between 1850-1852 by Leader & Cock in London.